Economic evaluation of a supported employment program for veterans with spinal cord injury. Issue 10 (7th May 2020) - Sutton, Bryce S.; Ottomanelli, Lisa; Njoh, Eni; Barnett, Scott; Goetz, Lance
Abstract: Objective: To estimate the net monetary benefit of an individual placement and support-based supported employment program for Veterans with spinal cord injuries. Design: Economic evaluation comparing a supported employment program to treatment as usual, using cost and quality-of-life data from a longitudinal study of Veterans with spinal cord injuries. Setting: Spinal cord injury centers in the Veterans Health Administration. Participants: Subjects ( N  = 213) who participated in a 24-month supported employment program at seven spinal cord injury centers. Supported employment participants were compared with a group of spinal cord injury Veterans who received treatment as usual in a prior study. Main outcome measures: Costs and quality-adjusted life years using the Veterans Rand-6 Dimension, estimated from the Veterans Rand 36-Item Health Survey. Results: The supported employment program was more effective at both 1- and 2-year periods compared with treatment as usual. Outpatient costs were significantly higher for supported employment, but inpatient costs were not significantly different from treatment as usual. When cost and effectiveness were compared jointly using net monetary benefit, a supported employment program following the core principles of Individual Placement and Supported employment was more effective but not cost-effective at standard willingness to pay thresholds. When we considered a sub-group of the supported employment participants who more closely resemble the treatment as usual group from a randomized trial, there was no significant difference in the cost-effectiveness of supported employment when compared to treatment as usual. Conclusions: With higher effectiveness and similar costs, supported employment for spinal cord injury Veterans has the potential to be cost-effective. Future studies need to randomize participants or carefully match participants based on observable patient characteristics to improve cost-effectiveness evaluations of this population. Implications for Rehabilitation: Supported employment as part of ongoing rehabilitation care helps individuals with spinal cord injury return to work and improve their quality of life. Many studies show that supported employment programs are cost effective for persons with mental disabilities, but there is only limited economic evaluation data on use of supported employment with persons with spinal cord injury. This study shows that supported employment integrated with ongoing rehabilitation care is more effective in restoring employment and health-related quality of life.